Cerebral blood flow increase in striatum by choreoathetosis: N‐isopropyl‐p‐[123I]iodoamphetamine single‐photon emission computed tomography findings. Issue 3 (May 2014) - Kikyo, Hideyuki; Yamamoto, Masahiro; Yamada, Hitoshi
Abstract A 75‐year‐old man presented choreoathetosis dominantly on his left side. Diffusion‐weighted imaging did not show abnormal intensities, whereas N‐isopropyl‐p‐[123I]iodoamphetamine single‐photon emission computed tomography showed a significant cerebral blood flow increase in the right striatum. The patient was treated with a D2‐blocker agent, and the choreoathetosis gradually decreased. The cerebral blood flow on the right striatum decreased by the following N‐isopropyl‐p‐[123I]iodoamphetamine single‐photon emission computed tomography. We discussed the mechanism of choreoathetosis from the perspective of the direct and indirect pathways in motor control.